USE OF FINANCIAL TECHNOLOGY AND THE ROLE OF FINANCIAL INCLUSION: A LITERATURE REVIEW - Baroto, Yatmoko; Prihatni, Rida; Gurendrawati, Etty (Cahaya Ilmu Bangsa, 2024)
This study aims to explore the relationship between financial technology (fintech), financial literacy, and financial inclusion, as well as their impact on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research employs a Systematic Literature Review (SLR) following PRISMA guidelines. Data were sourced from the Scopus database between 2018 and 2024, focusing on Q1 and Q2 journals. The search, using the keywords